The Forbidden Fruit: A Case of Tejocote (Crataegus mexicana) Supplement Toxicity - Cali Clark; Terrence Kelly; Kyle Mense; Shane Miller; Ashley Broce (Annals of Internal Medicine: Clinical Cases)
Supplement use continues to increase throughout the United States and as these compounds are not approved by the Food and Drug Administration, the side effect profiles are not well studied. Tejocote (Crataegus mexicana) is part of the hawthorn family and is a Mexican root supplement that is marketed for weight loss. We describe the case of a patient who ingested tejocote and presented with weakness, nausea, bradycardia with an atrioventricular block, and drug-induced thrombocytopenia.